Transcatheter aortic valve replacement via femoral artery for aortic regurgitation post-LVAD: a case report - Cheng, Shuai; Yang, Bin; Wang, Xiaoyu; Lian, Pingan; Song, Guangyuan; Zhang, Shenwei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundApproximately 25%–30% of patients experience aortic regurgitation (AR) within the first year after left ventricular assist device (LVAD) implantation. However, there is currently no consensus in clinical guidelines regarding the optimal treatment approach for LVAD-associated AR.Case summaryWe report a case of a female patient who developed AR following LVAD implantation. This patient exhibited an open-like configuration of left ventricular outflow tract (LVOT), with no calcified stenosis in the supravalvular region and a lack of anchoring anatomical structures at the junction of the LVOT and sinus-tubular junction. This anatomical configuration posed a high risk of prosthetic valve displacement during conventional transcatheter aortic valve replacement (TAVR). Therefore, we employed a novel TAVR system (Taurus Trio) equipped with a locator, which effectively prevented downward migration of the prosthetic valve after implantation.DiscussionThis case indicates the potential advantages and efficacy of the Taurus Trio valve in TAVR for AR Post-LVAD. We plan to conduct long-term follow-up to further explore and optimize the treatment protocol.